Banking Liberalization and its impact on Attracting Customers: applied research in a sample of Iraqi banks listed on the Iraq Stock Exchange (Journal of Accounting and Financial Studies ( JAFS ), 2021)
The research aims to shed light on banking liberalization and explain its impact on attracting customers, especially since Iraq adopted this policy after (2003) due to the changes that occurred, as the Central Bank of Iraq granted flexibility to banks in setting the interest rate on deposits and loans as well as allowing the entry of foreign banks in the local environment. The research relied on the analytical method for the dimensions of banking liberalization represented by (liberating interest rates, liberating credit, legal reserve requirements, entering foreign banks, privatization) as well as the factors affecting the attraction of customers, and a number of Iraqi banks listed in the Iraqi Stock Exchange were selected as a sample for research The duration of the research was determined from 2003-2019, and after the analysis, one of the most important findings of the research was that Iraq implemented the policy of banking liberalization after the issuance of the new banking law No. (94) for the year (2004) despite the difficulties that faced the country at that timeو One of the most important recommendations that came out of the research is the need to achieve security, political and economic stability for the development of the banking sector and the success of the policy of banking liberalization and benefit from its advantages to attract the largest number of customers.